Outcomes of resection of giant hepatocellular carcinoma in a tertiary institution: does size matter? - Thng, Yongxian (HPB (Oxford), 2015)
BACKGROUND: The surgical management of giant hepatocellular carcinoma (G-HCC), or HCC of ≥10 cm in diameter, remains controversial. The aim of this study was to compare the outcomes of surgical resection of, respectively, G-HCC and small HCC (S-HCC), or HCC measuring <10 cm. METHODS: A retrospective review of all patients (n = 86) diagnosed with HCC and submitted to resection in a tertiary hospital during the period from January 2007 to June 2012 was conducted. Overall survival (OS), recurrence rates and perioperative mortality at 30 days were compared between patients with, respectively, G-HCC and S-HCC. Prognostic factors for OS were analysed. RESULTS: The sample included 23 patients with G-HCC (26.7%) and 63 with S-HCC (73.3%) based on histological tumour size. Patient demographics and comorbidities were comparable. Median OS was 39.0 months in patients with G-HCC and 65.0 months in patients with S-HCC (P = 0.213). Although size did not affect OS in this cohort, the presence of satellite lesions [hazard ratio (HR) 3.70, P = 0.012] and perioperative blood transfusion (HR 2.85, P = 0.015) were negative predictors for OS. CONCLUSIONS: Surgical resection of G-HCC provides OS comparable with that after resection of S-HCC.